Use of signals of positive and negative selection to distinguish cancer genes and passenger genes - Bányai, László; Trexler, Maria; Kerekes, Krisztina; Csuka, Orsolya; Patthy, László (eLife, 2021)
A major goal of cancer genomics is to identify all genes that play critical roles in carcinogenesis. Most approaches focused on genes positively selected for mutations that drive carcinogenesis and neglected the role of negative selection. Some studies have actually concluded that negative selection has no role in cancer evolution. We have re-examined the role of negative selection in tumor evolution through the analysis of the patterns of somatic mutations affecting the coding sequences of human genes. Our analyses have confirmed that tumor suppressor genes are positively selected for inactivating mutations, oncogenes, however, were found to display signals of both negative selection for inactivating mutations and positive selection for activating mutations. Significantly, we have identified numerous human genes that show signs of strong negative selection during tumor evolution, suggesting that their functional integrity is essential for the growth and survival of tumor cells. The DNA in the cells of the human body is usually copied correctly when a cell divides. However, errors (mutations) are sometimes introduced during the copying process. Although the majority of mutations have no major impact on cells, many mutations are harmful: they decrease the ability of cells to survive. There are, however, mutations that can lead to cells dividing more frequently or gaining the ability to spread, which can lead to cancer. These mutations are known as ‘driver mutations’ because they drive the growth of tumors. Since such ‘driver mutations’ provide a growth advantage to tumor cells, they are subject to positive selection, this is, their frequency in the tumor increases over time. Because of their selective advantage, driver mutations accumulate at significantly higher rates than the neutral ‘passenger mutations’ that do not play a role in tumor growth. Genes that carry driver mutations are called driver genes, while genes that carry only passenger mutations are known as passenger genes. Certain genes, however, do not fit into either category. For example, some genes that are essential for tumor growth must get rid of harmful mutations to maintain activity. Mutations of such ‘tumor essential genes’ are thus subject to ‘negative’ or ‘purifying selection’. A major goal of cancer research is to identify genes that play critical roles in tumor growth. Earlier studies have identified numerous driver genes positively selected for driver mutations, exploiting the fact that driver genes show significantly higher mutation rates than passenger genes. Identification of tumor essential genes, however, is inherently more difficult since the paucity of mutations of negatively selected genes hinders the analysis of the mutation data. The failure to provide convincing evidence for negative selection in tumors has led to suggestions that it has no role in cancer evolution. Bányai et al. used a novel approach to address the question of whether negative selection occurs in cancer. Based on characteristic differences in the patterns of mutations in cancer they distinguished clusters of passenger genes, driver genes and tumor essential genes. The group of tumor essential genes includes genes that serve to satisfy the increased demand of rapidly dividing tumor cells for nutrients’ and genes that are essential for cell migration and metastasis (the spread of cancer cells to other areas of the body). The tumor essential genes that Bányai et al. identified may prove to be valuable targets for cancer therapy, illustrating the importance of genome sequencing in cancer research. Identification of additional tumor essential genes is, however, hindered by the fact that they are likely to have low levels of mutations, which can exclude them from meaningful analyses. Progress with genomic sequencing of tumors is expected to overcome this limitation and help identify additional genes that are essential for cancer growth.